2015
DOI: 10.7314/apjcp.2015.16.11.4589
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of the Dimer Forming Domain of the Caspase 8 Gene in Oral Submucous Fibrosis and Squamous Cell Carcinomas

Abstract: Background: Missense and frame-shift mutations within the dimer forming domain of the caspase 8 gene have been identified in several cancers. However, the genetic status of this region in precancerous lesions, like oral submucous fibrosis (OSMF), and well differentiated oral squamous cell carcinomas (OSCCs) in patients from southern region of India is not known, and hence the present study was designed to address this issue. Materials and Methods: Genomic DNA isolated from biopsy tissues of thirty one oral sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…CASP8 has been frequently found to be somatically altered in HNSCC and the CASP8 mutations are predominantly reported as truncating mutations (Maitra et al , ). It has also been reported an 8% of CASP8 mutation (2/25) in Indian oral cancer (Menon et al , ). On the contradictory, our study results revealed that there is no mutation in CASP8 in all the South Indian oral cancer samples screened.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…CASP8 has been frequently found to be somatically altered in HNSCC and the CASP8 mutations are predominantly reported as truncating mutations (Maitra et al , ). It has also been reported an 8% of CASP8 mutation (2/25) in Indian oral cancer (Menon et al , ). On the contradictory, our study results revealed that there is no mutation in CASP8 in all the South Indian oral cancer samples screened.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, a group from North India explored the PIK3CA mutations in oral cancer and documented a low prevalence of the PIK3CA mutations (~4%) in North Indian population (Shah et al , ). CASP8 mutation in oral cancer cell line has been identified first in our laboratory (Liu et al , ); subsequently, next‐generation sequencing of OSCC tumor samples found the CASP8 mutations (Maitra et al , ) and a study also documented the CASP8 mutations from India (Menon et al , ). NOTCH1 mutation has been frequently reported in oral cancer (Agrawal et al , ) including North Indian population (Maitra et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Using Sanger sequencing method, a study reported absence of CASP8 mutation in oral cancer samples collected from South Indian patients [23]. But another study, using same method on a different cohort from South India, reported that 8% of cancer patients had somatic mutations at CASP8 but none of the oral sub mucous fibrosis samples (one of the oral precancers) showed mutation [11]. It is to be noted that these two studies used Sanger sequencing method which is not suitable to detect low frequency somatic mutation in contrast to NGS method applied in this study (Fig 2).…”
Section: Discussionmentioning
confidence: 99%
“…Studies, using next generation sequencing (NGS) method, reported that mutations in CASP8 can vary from 7-34% in head and neck squamous cell carcinoma (HNSCC) across worldwide populations including India [7][8][9][10]. Based on Sanger sequencing method, another study on Southern Indian patient populations, reported 8% of oral cancer tissues had CASP8 mutations but none in oral sub-mucous fibrosis tissues (another oral precancerous lesion) [11]. CASP8 mutations with or without FAT1 mutations have been used as an important criterion for classifying mutational profiles of oral cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Over the recent past, attempts have been made to establish a potent diagnostic biomarker to explore the carcinogenesis underlying OSMF through IHC analysis. [ 5 ] The array of diagnostic markers studied using IHC in OSMF includes cell proliferation markers such as Ki 67 and cyclin D1,[ 5 6 ] tumor suppressor genes p53, p63, and p16,[ 6 7 ] transcription markers c-Jun, β-catenin, growth factor receptors c-Met and insulin-like growth factor II mRNA-binding protein 3 (IMP3),[ 5 ] epithelial to mesenchymal transition markers,[ 8 ] oncoproteins such as Bcl2,[ 9 ] apoptotic markers such as caspase 8, caspase 3,[ 10 11 ] cancer stem cell markers such as CD (cluster differentiation) 44,[ 12 ] pan endothelial markers associated with tumor angiogenesis CD34, CD105, growth factor markers such as basic fibroblast growth factor,[ 13 14 ] transforming growth factor-β1,TGF-β2,[ 15 ] cytokeratin markers such as CK 19,[ 16 ] and inflammatory markers such as cyclooxygenase (COX) 2. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%